STRATEGI IMPLEMENTASI BANTUAN LANGSUNG TUNAI DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT (STUDI KASUS DI DESA SEREANG) - Safitri, Vira; Mustanir, Ahmad; Barisan, Barisan (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This study aims to analyze the implementation strategy of Direct Cash Assistance(BLT) in improving community welfare, with a case study in Sereang Village,Maritengngae District, Sidenreng Rappang Regency. The BLT program is agovernment social intervention aimed at the poor and vulnerable as a form of socialprotection based on Village Funds. In its implementation, this program still faces anumber of obstacles such as inaccuracy of targets, low community participation insupervision, and not optimal data collection systems. This study uses a descriptivequalitative approach with George C. Edwards III's policy implementation theory,which includes four main indicators: communication, resources, executivedisposition, and bureaucratic structure. Data was collected through in-depthinterviews, observations, and documentation of village heads, village officials,hamlet heads, and communities receiving assistance. The results of the study showthat the BLT implementation strategy in Sereang Village is participatory andstructured, with the support of transparent public communication, adequate humanresources, and a positive implementation disposition. However, there are obstaclesin the form of not updating social data, the dependence of recipients on assistance,and lack of technical training for village officials. This study suggests strengtheningthe capacity of village bureaucracy, digitizing the data collection system, andeducating the public about the purpose of BLT as temporary assistance. With amore inclusive and responsive strategy, the implementation of BLT at the villagelevel is expected to be more effective in improving community welfare in asustainable manner.